Some Observations on the Demographic Variables of Marriage System in Greek Thrace: Evidence from Several Anthropological Populations - Konstantinos N. Zafeiris; Marianna Koukli (Genealogy, 2022)
The examination of demographic patterns and their variables is essential for our understanding of the anthropological and cultural processes that shape modern societies. Greek Thrace plays an important role in such analyses due to the cultural and socioeconomic variability it presents. This study is based on vital registration data of the 20th century, derived by various populations that inhabit the Department of Rhodopi, which are defined by discrete socio-economic, cultural, and historic backgrounds. We analyze and present various aspects of the social lives observed in these populations: marriage patterns, mean age at marriage of the spouses, mean age of mothers at first and last child, reproductive span, the children ever born, as well as other parameters related to reproduction. Our analyses show that several changes in marriage patterns have been undertaken throughout time, indicating an ongoing fertility transition. In that way, this study contributes to our knowledge on the anthropological populations from this part of Greece in relation to their socio-economic environment and it proposes possible analogies and differences that affected the evolution of the embedded populations.